Immobilization of Cu, Zn, Cd and Pb in mine drainage stream sediment using Chinese loess. (August 2017) - Zang, Fei; Wang, Shengli; Nan, Zhongren; Ma, Jianmin; Li, Yepu; Zhang, Qian; Chen, Yazhou
Abstract: The in situ immobilization of metal-contaminated sediment, using various amendments, has attracted great attention owing to their cost-effectiveness. The present study investigated the effectiveness of Chinese loess on Cu, Zn, Cd and Pb stabilization by decreasing their bioavailability in contaminated sediment. The loess was mixed with the sediment in doses of 0, 0.5, 1, 2, 5, 10 and 20 kg. Approximately 70 d after loess application, the effectiveness was evaluated using the Tessier sequential extraction procedure and single extractants, including ethylenediaminetetraacetic acid disodium salt (EDTA-2Na), diethylenetriaminepentaacetic acid (DTPA), calcium chloride (CaCl2 ) and hydrochloric acid (HCl). The results indicated that the loess can effectively transform Cu from the carbonate fraction into the residual fraction when the loess dose was ≥5 kg. However, loess had little effect on Zn, Cd and Pb immobilization. Correlation analysis showed that these four extractants can provide a good indication of the toxicity of Cu, Zn, Cd and Pb in the amended sediment. Additionally, the organic matter content in the amended sediment decreased by 1.4% for CK, 1.6% for L0.5, 1.7% for L1, 1.5% for L2, 1.5% for L5, 1.9% for L10 and 1.9% for L20 (CK: untreated sediment; L0.5 to L20 represent loess doses of 0.5, 1, 2, 5, 10 and 20 kg, respectively) compared to the initial organic matter content in the unamended sediment, which may increase the atmospheric carbon dioxide owing to the degradation of organic matter. Graphical abstract: Highlights: Chinese loess was firstly used as sorbent amendment to immobilize metals in sediment. Loess can effectively transform Cu from the carbonate into the residual fractions. Single extractants can predict the toxicity of metals in the amended sediment.